2010
DOI: 10.1007/s11999-010-1443-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased Chondrocyte Death after Steroid and Local Anesthetic Combination

Abstract: Background Hyaline articular cartilage has limited repair and regeneration capacity. Intraarticular administration of glucocorticoid and local anesthetic injections play an important role in the therapy of osteoarthritis. Glucocorticoids and anesthetics reportedly enhance apoptosis in chondrocytes, but effects of the combined use of glucocorticoids and local anesthetics are unknown. Questions/purposes We asked whether glucocorticoid and local anesthetic agents combined had any synergistic effects on chondrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 42 publications
7
109
0
2
Order By: Relevance
“…There were several reports about morphological influence of corticosteroids and inflammatory condition to the cartilage appearance. Farkas et al (32) reported that glucocorticoids and local anesthetics induced apoptosis in chondrocytes especially in the superficial layer of the osteochondral specimens. Fubini et al (33) also suggested that methylprednisolone suppressed matrix protein markers of chondrocytic differentiation and that the altered chondrocyte expression of matrix proteins likely contributed to the pathogenesis of corticosteroid-induced cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…There were several reports about morphological influence of corticosteroids and inflammatory condition to the cartilage appearance. Farkas et al (32) reported that glucocorticoids and local anesthetics induced apoptosis in chondrocytes especially in the superficial layer of the osteochondral specimens. Fubini et al (33) also suggested that methylprednisolone suppressed matrix protein markers of chondrocytic differentiation and that the altered chondrocyte expression of matrix proteins likely contributed to the pathogenesis of corticosteroid-induced cartilage degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The use of a cartilage culture medium instead is likely to have shown more toxicity with ropivacaine. Farkas et al 16 found that even ropivacaine can be harmful to articular cartilage when used at a higher concentration.…”
Section: 2mentioning
confidence: 99%
“…Injections of corticosteroid and local anesthetics combinations cause increased damage to chondrocytes. In an in-vitro and ex vivo study, Farkas et al have concluded that the combination of corticosteroid and local anesthetics has an increased adverse effect on articular chondrocytes (13,14). In an in-vitro study, Seshadri et al have shown a dose-and time-dependent decrease in chondrocyte viability after exposure to clinically relevant doses of methylprednisolone.…”
Section: öZetmentioning
confidence: 99%